2001
DOI: 10.1007/s100530170002
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization cross-sections of the first excited states of sodium and lithium in a magneto-optical trap

Abstract: A two element magneto-optical trap (MOT) for Na and Li-7 or Li-6 is used to cool and trap each of them separately. A fraction of the cold atoms is maintained in the first P-2(3/2) excited state by the cooling laser. These excited state atoms are ionized by laser light in the near-UV region, giving rise to a smaller number of trapped atoms and to different loading parameters. Photoionization cross-sections were derived out of these data. They are in reasonable agreement with data previously obtained using therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 0 publications
7
32
0
Order By: Relevance
“…Apart from extraterrestrial applications, we believe our results will contribute to the widening use of vapor-cell technology for producing better controlled Na MOTs in the range of tens of millions of atoms [16,17]. Indeed, * chandra.raman@physics.gatech.edu a recent preprint reports a vapor-cell-based sodium Bose-Einstein condensate (BEC) by rapid evaporation in a dipole trap, demonstrating that Zeeman slower technology is not required [18].…”
Section: Introductionmentioning
confidence: 88%
“…Apart from extraterrestrial applications, we believe our results will contribute to the widening use of vapor-cell technology for producing better controlled Na MOTs in the range of tens of millions of atoms [16,17]. Indeed, * chandra.raman@physics.gatech.edu a recent preprint reports a vapor-cell-based sodium Bose-Einstein condensate (BEC) by rapid evaporation in a dipole trap, demonstrating that Zeeman slower technology is not required [18].…”
Section: Introductionmentioning
confidence: 88%
“…Our group's hybrid trap consists of a standard vapor-cell Na MOT [41][42][43] concentric within a segmented LPT [44,45] and held in a vacuum chamber at a pressure ~1 0 _1° Torr. The MOT is loaded with 346 ± 3 K Na vapor from a biased getter source within the vacuum chamber.…”
Section: Magneto-optical Trapmentioning
confidence: 99%
“…In the temperature-limited regime [43,67], the volume of the MOT VMot remains constant while the MOT density n MOT increases linearly with atom population Na. Collisions between two MOT atoms lead to a nonexponential two-body loss rate /)wMOT [68], while collisions with constant density background Na atoms result in a linear loss rate yb.…”
Section: A Na Mot Loading Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramer et al [11] reported the saturated three-step resonance ionization of ground state and measured the photoionization cross section from the excited n 3 manifold of lithium. Wippel et al [12] reported the photoionization cross sections of the first excited states of two isotopes of lithium at different ionizing laser wavelengths above the threshold using a magneto-optical trap. Subsequently, Amin et al [13] measured the photoionization cross sections for the 3s, 2p, and 3d excited states of lithium at various ionizing laser wavelengths above the first ionization threshold using saturation absorption technique.…”
Section: Introductionmentioning
confidence: 99%